How and When Daily Abusive Supervision Affects Daily Organizational Citizenship Behavior for the Environment - Wang, Hongqing; Xiao, Jiuling (Frontiers in Psychology, 2022)
Organizational environmental sustainability depends primarily on employees’ organizational citizenship behavior for the environment (OCBE), and leadership plays an important role in improving and inhibiting employees’ OCBE. The purpose of the present study is to examine the mediation process by which abusive supervision affects employees’ OCBE through a daily diary study and to explore the boundary conditions of the relationship between daily moral disengagement and daily OCBE. We collected data from 112 Chinese employees for 10 consecutive days. The results show that daily abusive supervision has a significant negative effect on daily OCBE and that daily moral disengagement plays a significant mediating role in this relationship. In addition, the negative effect of daily moral disengagement on daily OCBE could be attenuated by a psychological green climate. Our findings support our hypotheses and offer useful theoretical and practical implications for promoting OCBE.